Inhibition of VDAC1 Rescues Aβ1-42-Induced Mitochondrial Dysfunction and Ferroptosis via Activation of AMPK and Wnt/β-Catenin Pathways - Xinpei Zhou; Ximin Tang; Tao Li; Dandan Li; Zhiting Gong; Xiujun Zhang; Yanjiao Li; Jianhua Zhu; Yong Wang; Bensi Zhang (Mediators of Inflammation)
Beta-amyloid (Aβ) accumulation in the brains of Alzheimer’s disease (AD) patients leads to mitochondrial dysfunction and ferroptosis in neurons. Voltage-dependent anion channel 1 (VDAC1) is a major protein in the mitochondrial outer membrane. It has been reported that VDAC1 associated with mitochondrial dysfunction and ferroptosis. However, the mechanism by which VDAC1 regulates mitochondrial dysfunction and ferroptosis of neurons in AD remains unclear. This study is aimed at investigating the mechanism of action of VDAC1 in mitochondrial dysfunction and ferroptosis in neurons of the AD model. In this study, we determined cell viability after treatment with Aβ1-42 via the MTT assay. The SOD, MDA, ROS, and MMP production was measured via the SOD kit, MDA kit, DCFDA staining, and JC-1 staining. The memory abilities of mice were detected via the Morris water maze test. The expression of AMPK/mTOR, Wnt/β-catenin, and GPX4 regulated by VDAC1 was detected via western blotting. Our present study showed that PC12 cells had decreased cell viability, increased LDH release, and decreased GPX4 expression after Aβ1-42 treatment. Meanwhile, Aβ1-42 induced MMP and SOD downregulation and increased MDA and ROS generation in PC12 cells. In addition, the expression of VDAC1 is increased in the brain tissue of AD mice and Aβ1-42-treated PC12 cells. Further investigation of the role of VDAC1 in regulating AD found that all effects induced by Aβ1-42 were reversed by inhibition of VDAC1. Additionally, inhibition of VDAC1 activates the AMPK/mTOR and Wnt/β-catenin pathways. Taken together, these findings demonstrate that inhibition of VDAC1 alleviates mitochondrial dysfunction and ferroptosis in AD neurons by activating AMPK/mTOR and Wnt/β-catenin.